Change in Body Weight and Long-Term Risk of Stroke and Death in Healthy Men. Issue 5 (May 2020) - Prestgaard, Erik; Mariampillai, Julian; Engeseth, Kristian; Erikssen, Jan; Bodegård, Johan; Liestøl, Knut; Kjeldsen, Sverre; Grundvold, Irene; Berge, Eivind
Abstract : Background and Purpose—: The importance of weight change for the risk of stroke is not well known. We examined the associations between early- and mid-life weight change and risks of stroke and death during long-term follow-up of healthy men. Methods—: We recruited healthy men aged between 40 and 59 years and performed a cardiovascular examination at baseline and again at 7 years. We collected data on weight change since the age of 25 (early-life weight change) and measured weight change from baseline to the visit at 7 years (mid-life weight change). For both weight change periods, participants were divided into the following categories: weight loss, weight gain 0 to 4.9 kg, weight gain 5 to 9.9 kg, and weight gain ≥10 kg. Data on stroke and death were collected up to 35 years, from study visits, hospital records, and the National Cause of Death Registry. We used Cox regression to analyze the associations between weight change during early-life and mid-life and risks of stroke and death. Results—: Of the 2014 participants, 2014 (100%) had data on early-life weight change and were followed for a median of 30.1 years, while 1403 had data on mid-life weight change and were followed for a median of 24.6 years. During early-life, compared with those who had weight gain 0 to 4.9 kg, hazard ratio for stroke was 1.46 (95% CI, 1.09–1.95) among those with weight gain 5 to 9.9 kg, 1.39 (95% CI, 1.03–1.87) for those with weight gain ≥10 kg, and 1.46 (95% CI, 0.99–2.11) among those with weight loss. For all-cause death, the hazard ratios were 1.08 (95% CI, 0.92–1.23), 1.14 (95% CI, 0.98–1.33), and 1.29 (95% CI, 1.06–1.56), respectively. During mid-life, there were no significant differences in risk of stroke or death between the groups. Conclusions—: Weight increase during early-life, but not mid-life, seems to be associated with increased long-term risk of stroke in healthy men. If these findings can be confirmed, efforts to prevent weight increase should target the younger population. Abstract : Supplemental Digital Content is available in the text.